Threaded block-parallel algorithm for finding the shortest paths on graph - O. N. Karasik; A. A. Prihozhy (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The problem of finding the shortest paths on weighted graphs is considered. The variants of statement of the problem, known algorithms for it solving, areas of practical application and existing challenges, in particular, the challenge of scalability, are analyzed. The class of block-parallel algorithms, their advantages and disadvantages is investigated. A fast block-parallel threaded algorithm oriented to large-sized graphs is proposed. It differs by changing the order of block calculations, reducing the critical path and operating time on a multi-core system, decreasing the data exchanges among local caches of cores and between neighbor levels of hierarchical memory.